The potential of ERCoRe learning model on students' creative thinking skills - Mustaqim Mustaqim; Ismirawati Ismirawati; Arsad Bahri (JPBIO (Jurnal Pendidikan Biologi), 2022)
21st Century provides many challenges, especially for the world of education. Students are expected to acquire several skills that can support their lives in order to compete in the future. One important skill is creative thinking skills. Creative thinking skills are a way of thinking based on information to find solutions to a problem that is emphasized on the quantity, appropriateness and diversity of answers. Some observations show the low creative thinking skills of students because the empowerment of creative thinking skills is still lacking in learning in Indonesia. One solution that can be done in improving creative thinking skills is to choose the right learning model in this case the researcher uses the ERCoRe learning model. This study aims to look at the effect of the ERCoRe learning model on students' critical thinking skills. This type of research is quasi-experimental. Analysis of the data used is covariance analysis. Conclusions based on the results of the analysis there is an effect of 52,006 on the ERCoRe learning model while the conventional learning model is only 43,515 on students' critical thinking skills compared to conventional strategies.